Forage crops status, determinants and constraints: Current status of improved forage crops, determinants and constraints on smallholders mixed crop-livestock farms in the semi-arid region of Algeria - Lounis Semara; Charefeddine Mouffok; Farida Belkasmi (Journal of Agriculture and Environment for International Development)
In Algeria, forage crops face significant limitations, posing a challenge to the development of intensive livestock production. This study aims to understand the status, determinants, and constraints to the adoption of improved forage crops in mixed crop-livestock family farms in the province of Bordj Bou Arreridj, located in the semi-arid zone of eastern Algeria.  We conducted a survey on 98 farms using a semi-structured questionnaire in two different ago-pedoclimatic zones, and our analysis included the description of forage cropping modalities and the empirical modelling of the factors influencing the adopted patterns of forage crops. Our results showed that fodder crops cover almost 20% of the total arable land. However, the allocation of land to forage crops varied considerably between farms and zones. Cultivated forage crops included barley, oats, corn, sorghum, and alfalfa. The adoption of improved fodder crops was influenced by several structural and socio-economic factors, such as exploited farmland size, size of sheep livestock, family labor size, access and permanent availability of irrigation water, farming equipment, social network involvement, and agricultural training. The development of forage crops encountered various constraints, including issues of seed availability and cost, limited farmland, and insufficient irrigation water. To boost forage incorporation in local farming systems, it is imperative to raise farmers' awareness of the agronomic benefits of cultivating fodder crops. In addition, supporting farmers to improve their knowledge, farm structures, and equipment and providing seeds and fertilizers are crucial for the successful promotion of fodder crops.